Return on Assets of Construction Sector Companies Moderates The Determinants of Tax Avoidance - Nani Rohaeni; Sari Putri Pertiwi; Eva Fitri Andriani; Amartya Nadhia Annisa (Southeast Asian Journal of Science and Technology, 2024)
This research aims to determine and test the influence of fixed asset intensity and institutional ownership on tax avoidance and the moderating effect of ROA on the influence of fixed asset intensity and institutional ownership on tax avoidance. This research method uses descriptive quantitative methods with data in the form of financial reports from the BEI website. The research population includes 26 construction sector companies on the IDX for the 2019-2023 period, and a sample of 13 companies was selected using purposive sampling. The data analysis carried out was MRA regression with Eviews 12. The results of the data analysis showed that the influence of fixed asset intensity on tax avoidance had a probability value of 0.03890.05. The influence of fixed asset intensity on tax avoidance is moderated by ROA, obtaining a prob value of 0.00010.05. The conclusion is that fixed asset intensity influences tax avoidance. ROA can moderate the influence of fixed asset intensity on tax avoidance. Meanwhile, institutional ownership does not affect tax avoidance, and ROA cannot moderate the effect of institutional ownership on tax avoidance.